Impact of COVID-19 on the Hygiene Practices of Adolescent in Makkah-KSA - Salma Salem Alqurashi; Amani Abdulrasheed Bakhsh; Hala Y. Ali, (British Journal of Healthcare and Medical Research, 2023)
Background: Since the Makkah region is a sacred place for Muslims worldwide due to Holy Mosque, it is considered the busiest place globally. Adolescents are ‘silent carriers’ of COVID-19 infection, and they require knowledge about proper hygiene practices. Aims: It is necessary to assess the impact of COVID-19 on adolescents’ hygiene practices in Makkah. Subjects and Methods: A cross-sectional quantitative research method was used. The adolescents included in this study were primary, secondary and university students with ages ranging from 10 to 19. All subjects were from the Makkah region. The research variables comprised general hygiene, household hygiene, food-related hygiene, hand hygiene techniques and personal hygiene. Sample: A sample population of 303 adolescents. Setting: The research was conducted in primary, intermediate and secondary schools and among first-year university students in Makkah. Tools: The questionnaire was taken from Stevenson (2009) to evaluate perceptions about hygiene practices. Results: The results indicate a prominent difference between personal hygiene practices among adolescents before and after the COVID-19 pandemic. The intermediate level students showed a significant change in hygiene practices, while female adolescents were more concerned with hygiene than male adolescents. The knowledge collected from this study is important because it addresses changes to adolescent health, hygiene and psychology during the pandemic. Conclusion: Adolescents’ hygiene practices were affected by the COVID-19 pandemic in Makkah. Recommendations: Although the findings were informative, further exploration using qualitative methods would enhance a greater understanding of the problem. Many parameters need to be explored to further explain the respondents’ change in behaviours in terms of handling the pandemic situation. The researchers could use other studies to understand the hygiene situation during the pandemic.